Valine deficiency has a greater impact on broiler growth and bone health than isoleucine deficiency - Doyun Goo; Woo Kyun Kim (Poultry Science)
Valine and isoleucine are not only two of the indispensable amino acids (AAs) in chickens but also have special mechanisms with leucine within the branched-chain AA (BCAA) category. Therefore, we aimed to investigate how valine or isoleucine deficiency could specifically affect growth performance in broilers through various analyses. A total of 252 seven-day (d)-old male Cobb 500 broilers were allotted to three treatments with six replicates and reared until d 21. The three treatments were as follows: (1) Control group (CON; 1.31 leucine:lysine ratio), (2) valine deficiency group (-VAL; 0.62 valine:lysine ratio and 85% valine level compared to the CON group), and (3) isoleucine deficiency group (-ILE; 0.54 isoleucine:lysine ratio and 85% isoleucine level compared to the CON group). The -VAL group had significantly decreased d 7, 14, and 21 body weight (BW), BW gain (BWG), feed intake (FI), and feed efficiency from d 7 to 21 compared to the CON and -ILE groups (P < 0.001). The -ILE group showed no difference in d 14 and 18 BW; however, they showed significantly reduced BW and BWG at d 21 and feed efficiency from d 7 to 21 compared to the CON group (P < 0.001). Daily FI in the -VAL group significantly decreased from the beginning compared to the two groups, and this gap further expanded until d 21. The -VAL group also had significantly decreased breast muscle weight, total tissue weight, bone mineral density, bone mineral content, and walking ability (P < 0.01). The expression levels of mechanistic target of rapamycin and BCAA catabolism-related genes were highest in the -VAL group (P < 0.05), whereas the -ILE group did not show any difference compared to the CON group (P > 0.05). In conclusion, about 85% valine deficiency is accompanied by a substantial reduction in chicken growth, which has a much greater effect than isoleucine. Valine deficiency can also lead to increased utilization of leucine, which may result in BCAA antagonism.